2004
DOI: 10.17221/4045-pse
|View full text |Cite
|
Sign up to set email alerts
|

Successional dynamics of Cynosurus pasture after abandonment in Podkrkonoší

Abstract: Between 1996Between -2002, successional dynamics on an abandoned pasture in Přední Ždírnice (lat. 50°32'N, long. 15°40'E) was examined. A 7-year study was performed on the abandoned mesotrophic pasture classified as Cynosurion Tüxen 1947 at the start of the study. Two permanent plots (100 m 2 ) were established and sampled three times a year; changes in plant species composition (species cover) and plant species diversity (species number) were studied. Species assemblages of the Cynosurus pasture were describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Another advantage of long-term permanent plot experiments is that they enable us to study the interaction between restoration treatments and the spontaneous dynamics of the vegetation. According to our knowledge, all previous studies reported about the spread of C. epigejos (Aiken et al 1989;ten Harkel & van der Meulen 1995;Rebele & Lehmann 2001;Sedláková & Fiala 2001;Házi & Bartha 2002;Holub 2002;Luoto et al 2003, Stránská 2008 and no published study has found the reverse trend. In our experiment, we found a significant decrease of the cover of C. epigejos also in the control plots.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…Another advantage of long-term permanent plot experiments is that they enable us to study the interaction between restoration treatments and the spontaneous dynamics of the vegetation. According to our knowledge, all previous studies reported about the spread of C. epigejos (Aiken et al 1989;ten Harkel & van der Meulen 1995;Rebele & Lehmann 2001;Sedláková & Fiala 2001;Házi & Bartha 2002;Holub 2002;Luoto et al 2003, Stránská 2008 and no published study has found the reverse trend. In our experiment, we found a significant decrease of the cover of C. epigejos also in the control plots.…”
mentioning
confidence: 83%
“…Related problems were reported from central Europe (Rebele & Lehmann 2001;Sedláková & Fiala 2001;Házi & Bartha 2002;Holub 2002;Luoto et al 2003;Somodi et al 2004Somodi et al , 2008Stránská 2008), from western Europe (ten Harkel & van der Meulen 1995), and also from north America (Aiken et al 1989).…”
Section: Introductionmentioning
confidence: 99%
“…The growing abundance of an expansive species may strongly change the quantitative proportions between species as well as spatial properties of the sward. In Central Europe, one such species is Calamagrostis epigejos (wood small-reed), whose expansion often leads to the degradation of vegetation of abandoned or irregularly managed meadows [9,[13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, only one species Achillea millefolium was characteristic of control plots. Indicator value analysis evidenced that abandoned sheep pens induced only qualitative changes in plant communities (Stránská 2004). Quantitative changes (in species number) were not detected.…”
Section: Discussionmentioning
confidence: 88%